An Analysis of Problems and Solutions in the Low Level of Cash Waqf in Indonesia Using Analytic Network Process (ANP) - Aprida Susanti; Dede Fatah; Zulkarnain Muhammad Ali (Faculty of Islamic Business and Management, 2025)
The low level of cash waqf mobilization in Indonesia presents a significant challenge for Islamic philanthropy, attributed to various internal and external factors. This study addresses the gap in existing literature concerning the comprehensive analysis of factors that impact the low uptake of cash waqf and the strategic management approaches necessary to address these challenges. While previous research has examined aspects of cash waqf, there remains a need for a systematic approach that integrates problem, solution, and strategy analysis through the Analytic Network Process (ANP) method. The objectives of this study are to identify the key factors affecting cash waqf mobilization and to propose detailed solutions and strategies for effective management. Utilizing the ANP framework and the Problem-Solution Model, the study collects data from a sample of 7 experts and 7 practitioners. The analysis considers four dimensions—human resources, institutional frameworks, government, and society—and is organized into three clusters: problems, solutions, and strategies, with a focus on both internal and external factors. Key findings indicate that the low mobilization of cash waqf is primarily due to weak management systems within institutions. The study proposes that enhancing the Indonesian Waqf Board (BWI) through governmental support is a critical solution, while the application of information technology is identified as the main strategic priority. The study underscores the need for the government (particularly BWI) and waqf institutions (nazhir) to prioritize a robust cash waqf ecosystem through improved management, professionalization, literacy, and resource allocation. This research contributes to the limited body of literature on cash waqf mobilization by providing a comprehensive model for addressing both internal and external challenges, thereby offering valuable insights for Islamic finance policymakers and practitioners.